Mechanical and structural behavior of as-built and post treated Ti6Al4V lattice structures fabricated by selective laser melting (SLM) - Salem, Hala Ahmed (AUC Knowledge Fountain, 2020)
Lattice structure is a type of cellular structures that is composed of repeatable unit cells, each of which is formed of interconnect network of struts. Lattices with different structures are gaining attention for their good mechanical properties for light weight applications. Selective laser melting (SLM), is one of the AM powder-bed fusion fabrication techniques. SLM is widely known for its capability for fabricating complex metallic structures such as lattice structures with high resolution. SLM process influence the microstructure and mechanical properties of fabricated parts. The used processing parameters influence the level of internal porosity within the fabricated parts which directly influence the mechanical properties. Accordingly, it is essential to select the suitable parameters for fabrication. SLM processing also influences the phases and microstructure of the fabricated alloys, an example of which is Ti-alloys. Accordingly, in an attempt to develop a better understanding for the influence of SLM processing parameters on the fabricated lattice structures, a wide range of processing parameters (lase power and scanning speed) were used to fabricate Ti6Al4V BCC lattice structure. 25 processing combination were investigated in terms of strut size, structural porosity and internal porosity. Moreover, the developed internal porosity morphology was examined, for which a process map was developed that outlined the type of defect formed defects within the fabricated conditions. Five zones depicted the types of formed defects, which were the gas porosity zone, keyholing zone, irregular and gas defects zone, and lack of fusion defects zone. Quantitative and qualitative analysis facilitated the selection of the processing parameters that was suitable for producing lattice structure with minimum level of internal porosity, structural porosity close to the designed target and strut size almost equal the designed size. The SLM power and scanning speed processing parameters selected were 100W and 1600mm/s, respectively. Characterization of the as-built condition with the selected SLM processing parameters was conducted including microstructural analysis, mechanical behavior characterization and fracture mechanism were investigated. Influence of post SLM processing treatments using Hot isostatic Pressing (HIP) and Heat Treatment (600-800 oC) on the phase transformation and mechanical properties were investigated compared to the as-built condition. Results revealed the decomposition of α՝ depending on the heating temperature used, which was reflected in the reduction of the yield strength. Additionally, reduction in ductility was observed as well in all the treated condition due to the oxygen diffusion which reduced the strain at fracture. This was attributed to the formation of Ti3Al precipitates in case of heat treatment at 600 oC , 730 oC. As for HIPing treatment and heat treatment at 800 oC the reduction in ductility was attributed to the formation of alpha-casing along the edge of the lattice struts and α phase through the boundaries leading to brittle failure of the fabricated parts.